(untitled) (Research, Society and Development, 2022)
The objective of this text regard the possibility of applying sustainable territorial development principles to the territories affected by the West-East Integration railroad, which extends from the municipality of Figueirópolis, in Goiás, to Ilhéus in Bahia, a route of over 1500 km, crossing very heterogeneous biomes and ecosystems. In its elaboration, an attempt was made to deepen the meanings of territory, territoriality, environment, development and sustainable development to evidence their adaptability to public or private interventions brought from the railroad. The material or object of research consists of the set of official documents generated in the studies that preceded the works and countless academic texts or texts prepared in the sphere of civil society. The methodological procedures include a literature review, analysis, organization and interpretation of data with a view to supporting the assumptions or hypotheses of applicability of sustainability precepts to the aforementioned interventions, whether they are aimed at the productive segments, service provision, infrastructure, etc. The result is expected to stimulate the debate on the importance of sustainable territorial development and interest public agencies that will promote interventions along the railway route.